2021
DOI: 10.1007/s00018-021-04021-3
|View full text |Cite|
|
Sign up to set email alerts
|

Novel interaction between neurotrophic factor-α1/carboxypeptidase E and serotonin receptor, 5-HTR1E, protects human neurons against oxidative/neuroexcitotoxic stress via β-arrestin/ERK signaling

Abstract: Protecting neurons from death during oxidative and neuroexcitotoxic stress is key for preventing cognitive dysfunction. We uncovered a novel neuroprotective mechanism involving interaction between neurotrophic factor-α1 (NF-α1/carboxypeptidase E, CPE) and human 5-HTR1E, a G protein-coupled serotonin receptor with no previously known neurological function. Co-immunoprecipitation and pull-down assays confirmed interaction between NFα1/CPE and 5-HTR1E and 125I NF-α1/CPE-binding studies demonstrated saturable, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 48 publications
3
40
0
Order By: Relevance
“…We propose that CPE controls its targets, such as c-MYC and Cyclin D1, through binding a receptor to activate downstream signaling. We have recently found that CPE activates a receptor HTR1E to activate the ERK pathway [ 48 ]. ERK/c-MYC and ERK/Cyclin D1 signaling are well known in promoting proliferation and migration in cancer cells, and HTR1E has been found in human cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that CPE controls its targets, such as c-MYC and Cyclin D1, through binding a receptor to activate downstream signaling. We have recently found that CPE activates a receptor HTR1E to activate the ERK pathway [ 48 ]. ERK/c-MYC and ERK/Cyclin D1 signaling are well known in promoting proliferation and migration in cancer cells, and HTR1E has been found in human cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Protecting neurons from death during oxidative and neuroexcitotoxic stress is key for preventing cognitive dysfunction [ 27 ]. Oxidative stress can promote the production of Aβ, promote cell apoptosis, and reduce the expression of LDL-C receptor related protein 1 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular modeling studies predicted that NF-α1/CPE interacts with 5-HTR1E, outside of its serotonin pocket, and stabilized by several salt bridges and hydrogen bonds. Moreover, molecular dynamic studies revealed strong coupling of the intracellular loop 3 of HTR1E with β-arrestin1, indicating potential activation of β-arrestin1 ( Sharma et al, 2021 ). Immunohistochemical analysis of human hippocampus showed that NFα1/CPE and 5-HTR1E were colocalized on the cell membrane of neurons, suggesting a functional role.…”
Section: Role Of Neurotrophic Factor-α1/carboxypeptidase E and Its Re...mentioning
confidence: 99%
“…In addition, co-immunoprecipitation, and pull-down assays in HEK293 cells indicate that NFα1/CPE binds with 5-HTR1E in a saturable, high-affinity manner, with a Kd 13.82 nM. Cell biological studies demonstrated that NF-α1/CPE exerted protective activity against oxidative stress in HEK293 cells by interacting with 5-HTR1E and activating downstream β-arrestin/ERK/CREB/BCL2 signaling cascade ( Sharma et al, 2021 ). Furthermore, studies showed that NFα1/CPE treatment decreased cytotoxicity induced by oxidative stress in primary human neurons, but not when HTR1E expression was knocked-out in these neurons ( Sharma et al, 2021 ).…”
Section: Role Of Neurotrophic Factor-α1/carboxypeptidase E and Its Re...mentioning
confidence: 99%
See 1 more Smart Citation